Pengaruh Pemberian Posisi Semi Fowler terhadap Peningkatan Saturasi Oksigen pada Pasien Congestive Heart Failure (CHF) di Ruang Intensive Care Unit (ICU) Rumah Sakit Mekar Sari - Kusnanto Kusnanto; Pathul Arip (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Congestive heart failure (CHF) is a condition that not only involves a disorder in one system, but also causes the heart to be unable to pump or meet the body's metabolic needs. Clinical symptoms that may be experienced by CHF patients include shortness of breath, orthopnea, shortness of breath during activity, ascites and pulmonary edema. This condition can be detected through oxygen saturation monitoring, and is considered present if the patient's oxygen saturation level is below 95%. To optimize oxygen saturation in CHF patients, one effective strategy is to change the position of the body. The purpose of this study is to determine the effect of giving a semi-fowler position on increasing oxygen saturation in patients with Congestive Heart Failure (CHF) in the Intensive Care Unit (ICU) Room of Mekar Sari Hospital. This study uses a quasi-experimental research design with a one-group pre-post test design without control approach, which is a study conducted with intervention in one group without a comparator conducted in January 2024. The population in this study is Congestive Heart Failure (CHF) patients in the Intensive Care Unit (ICU) Room of Mekar Sari Hospital in January 2025. And the method used in this sampling was carried out by the purposive sampling method of 20 respondents. Data collection uses observation sheets and saturation oximetry used to measure pretest and posttest oxygen saturation. Data analysis was univariate (frequency distribution) and bivariate (Paired Sample Test). The results of sig (2-tailed) in the relationship between Pre Test and Post Test using the Wilcoxon Test are 0.000 ( 0.05) or smaller than alpha 0.05, then it can be decided that the test result is H0 rejected and Ha accepted. Therefore, it was concluded that there was an effect of giving a semi-fowler position on increasing oxygen saturation in patients with Congestive Heart Failure (CHF) in the Intensive Care Unit (ICU) Room of Mekar Sari Hospital. The results of this study can be used as a recommendation for nurses to be able to provide a semi-fowler position in patients with Congestive Heart Failure (CHF) so that oxygen saturation increases.  Keywords: Congestive Heart Failure, Semi Fowler Position, Oxygen Saturation. ABSTRAK Gagal jantung kongestif (CHF) adalah kondisi yang tidak hanya melibatkan gangguan pada satu sistem, tetapi juga menyebabkan jantung tidak mampu memompa atau memenuhi kebutuhan metabolik tubuh. Gejala klinis yang mungkin dialami oleh pasien CHF mencakup sesak napas, ortopnea, sesak napas saat aktivitas,asites,edema paru. Kondisi ini dapat dideteksi melalui pemantauan saturasi oksigen, dan dianggap ada jika tingkat saturasi oksigen pasien di bawah 95%. Untuk mengoptimalkan saturasi oksigen pada penderita CHF, salah satu strategi yang efektif adalah mengubah posisi tubuh. Tujuan penelitian ini untuk mengetahui pengaruh pemberian posisi semi fowler terhadap peningkatam saturasi oksigen pada pasien Congestive Heart Failure (CHF) Di Ruang Intensive Care Unit (ICU)  Rumah Sakit Mekar Sari. Penelitian ini menggunakan desain penelitian quasi eksperimen dengan pendekatan one group pre-post test design without control yaitu penelitian yang dilakukan dengan intervensi pada satu kelompok tanpa pembanding yang dilakukan pada bulan Januari 2024. Populasi pada penelitian ini adalah pasien Congestive Heart Failure (CHF) Di Ruang Intensive Care Unit (ICU) Rumah Sakit Mekar Sari pada bulan Januari 2025. dan metode yangdigunakan dalam pengambilan sampel ini dilakukan dengan metode purposive sampling berjumlah 20 responden. Pengambilan data menggunakan lembar observasi dan oxymetri saturasi yang digunakan untuk mengukur saturasi oksigen pretest dan posttest. Analisis data secara univariat (distribusi frekuensi) dan bivariat (uji Wilcoxon). Didapat hasil sig (2-tailed) pada hubungan Pre Test dan Post Test dengan menggunakan Uji Wilcoxon yaitu sebesar 0,000 ( 0,05) atau lebih kecil dari alpha 0,05 maka dapat diambil keputusan bahwa hasil pengujian adalah H0 ditolak dan Ha diterima. Sehingga disimpulkan terdapat pengaruh pemberian posisi semi fowler terhadap peningkatan saturasi oksigen pada pasien Congestive Heart Failure (CHF) Di Ruang Intensive Care Unit (ICU)  Rumah Sakit Mekar Sari. Hasil penelitian ini dapat dijadikan rekomendasi bagi perawat agar dapat memberikan posisi semi-fowler pada pasien Congestive Heart Failure (CHF) agar saturasi oksigen meningkat. Kata Kunci: Congestive Heart Failure, Posisi Semi Fowler, Saturasi Oksigen.